The Comparison of Clinical and Surgical Staging of Cervical Cancer: A Retrospective Study on Patients at Dr. Cipto Mangunkusumo General Hospital, Jakarta, Indonesia - Bram Pradipta (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To evaluate the accuracy of clinical examination in determining the stage of operable cervical cancer and the extent of the disease. Method: The study involved 58 subjects from outpatient, emergency unit, and ward of Department of Obstetrics and Gynecology Dr. Cipto Mangunkusumo Hospital, from January 2008 to December 2010 with a diagnosis of cervical cancer. Patients who were diagnosed with cervical cancer up to stage IIA were included and patients lost to follow-up, receiving preoperative neo-adjuvant chemotherapy, and died before getting treatment were excluded. The outcomes evaluation were postoperative clinical staging, including the presence of enlarged lymph nodes, parametrial involvement, and tumor size. Lymph nodes, parametrial, and the tumor size were assessed from the surgery and pathological anatomy results. Result: The age distribution of 58 subjects ranged from 25 to 70 years (mean 48.39 years, SD 8.82). Squamous cell carcinoma was the most frequent type (44.9%), followed by adenocarcinoma (24.1%). Errors in preoperative clinical staging compared with postoperative was 40% in stage IA1, 9.52% in stage IB1, 17.65% in stage IB2, and 7.14% in stage IIA. Sensitivity, specificity, positive predictive value, and negative predictive value for preoperative clinical examination of lymph nodes were 11.1%, 100%, 100%, and 85.96%. Sensitivity, specificity, positive predictive value, and negative predictive value for preoperative clinical examination of parametrial involvement were 37.5%, 100%, 100%, and 90.90%. Sensitivity, specificity, positive predictive value, and negative predictive value for preoperative clinical examination of the tumor size were 91.84%, 88.89%, 97.83% and 66.67%. Conclusion: Clinical examination has limitation, especially in determining lymph nodes and parametrial involvement. Other diagnostic modalities in determining the extent of the disease is necessary. Enforcement of the right diagnosis in patients with cervical cancer is needed to determine the appropriate treatment. [Indones J Obstet Gynecol 2011; 35-1: 25-9] Keywords: staging, cervical cancer, preoperative, postoperative